(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Income Tax (PPh) Article 26 is an essential part of Indonesia’s tax system, imposed on income received by foreign taxpayers from sources within Indonesia. The purpose of this study is to evaluate the effectiveness of the implementation of Article 26 in international transactions, focusing on tax withholding mechanisms, taxpayer compliance, and the significance of Double Tax Avoidance Agreements (DTAAs). The methodology used is descriptive-qualitative, with case studies conducted in several companies engaged in international transactions. The findings indicate that although the provisions of Article 26 are relatively clear, there are still administrative challenges and issues of interpretation related to international taxation that may result in lost opportunities for tax revenue. Furthermore, the use of DTAAs by foreign taxpayers often reduces the tax burden that should be imposed, thus requiring a thorough evaluation of their implementation. The recommendations of this study include strengthening tax supervision, digitalizing tax administrative processes, and enhancing education for tax withholders to ensure a more effective and equitable application of Article 26. Keywords: Article 26 Income Tax, international transactions, foreign taxpayers, tax withholding, DTAAs.